Physiological Response of Vi tis vinif era L. ( cv. Chenin blanc) Grafted onto Different Rootstocks on a Relatively Saline Soil - Southey, J.M.; Jooste, J.H. (South African Journal of Enology and Viticulture, 2017)
Certain physiological parameters, namely leaf water potential, stomatal resistance and rate of photosynthesis of Chenin blanc grafted onto 10 rootstock cultivars on a relatively saline soil under irrigation in a hot region (V), were measured for two growing seasons. Soil electrical resistance, which varied from 632 to 271 ohms in the shallower soil layers (<500mm) and from 414 to 167 ohms deeper in the soil, decreased during the growing seasons. Although diurnal and seasonal patterns of change of the physiological parameters measured did not differ between rootstock cultivars, significant differences in their magnitudes were apparent. The rootstocks US 16-13-23, 13-5 E.V.E. Jerex were more stressed than 101-14 Mgt, 143-B Mgt and 110 Richter and had lower rates of photosynthesis. Photosynthetic rate was predominantly inversely correlated with stomatal closure. The use of 101-14 Mgt and 143-B Mgt is recommended under relatively saline conditions.